2011
DOI: 10.1088/0004-637x/734/1/54
|View full text |Cite
|
Sign up to set email alerts
|

THE RADIO-2 mm SPECTRAL INDEX OF THE CRAB NEBULA MEASURED WITH GISMO

Abstract: We present results of 2 mm observations of the Crab Nebula, obtained using the Goddard-IRAM Superconducting 2 Millimeter Observer (GISMO) bolometer camera on the IRAM 30 m telescope. Additional 3.3 mm observations with the MUSTANG bolometer array on the Green Bank Telescope are also presented. The integrated 2 mm flux density of the Crab Nebula provides no evidence for the emergence of a second synchrotron component that has been proposed. It is consistent with the radio power law spectrum, extrapolated up to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
3
24
0
Order By: Relevance
“…4 We indicate in the plot the SNR (870 yr, Bietenholz & Bartel 2008) and spindown (4800 yr, Camilo et al 2006) ages for this PWN. 5 A mid-IR bump over the power-law fit in the Crab spectrum in the mid-IR at ∼50 μm is due to thermal emission from the warm dust generated by the SN (Temim et al 2006;Arendt et al 2011;Temim et al 2012). 6 The optical-IR part of the 3C 58 torus spectrum is confirmed by near-UV and near-IR observations (Zyuzin et al, in prep.).…”
Section: Multiwavelength Spectrum Of the Torus-like Pwnmentioning
confidence: 88%
See 1 more Smart Citation
“…4 We indicate in the plot the SNR (870 yr, Bietenholz & Bartel 2008) and spindown (4800 yr, Camilo et al 2006) ages for this PWN. 5 A mid-IR bump over the power-law fit in the Crab spectrum in the mid-IR at ∼50 μm is due to thermal emission from the warm dust generated by the SN (Temim et al 2006;Arendt et al 2011;Temim et al 2012). 6 The optical-IR part of the 3C 58 torus spectrum is confirmed by near-UV and near-IR observations (Zyuzin et al, in prep.).…”
Section: Multiwavelength Spectrum Of the Torus-like Pwnmentioning
confidence: 88%
“…This cannot be excluded even for the Crab, where, in addition to the significant X-ray-optical slope change, some small breaks may exist between the optical and near-IR and/or between the near-IR and mid-IR (Arendt et al 2011). In Fig.…”
Section: Multiwavelength Spectrum Of the Torus-like Pwnmentioning
confidence: 99%
“…One way to estimate B is based on the synchrotron break frequency in the integrated spectrum (Equation (7)). However, the break is not a sharp feature and it is difficult to locate the synchrotron break frequency of the Crab and 3C 58 based on current observational data (Slane et al 2008;Arendt et al 2011). Another way is to model the high-energy inverse Compton emission.…”
Section: Pure Diffusion Modelmentioning
confidence: 99%
“…In the millimetre wavelength range, we used the Goddard-IRAM Superconducting 2 Millimeter Observer (GISMO, Staguhn et al 2006) 2 mm data observed on the IRAM 30 m telescope, and Multiplexed Squid TES Array at Ninety GHz (MUSTANG, Dicker et al 2008) 3.3 mm observations obtained with the Green Bank Telescope (GBT). The data sets, observational details and data reduction strategy have been presented in detail in Arendt et al (2011). At 2 mm, Arendt et al (2011) reported a total integrated flux density of 244±24 Jy.…”
Section: Millimetre and Radio Observationsmentioning
confidence: 99%
“…The data sets, observational details and data reduction strategy have been presented in detail in Arendt et al (2011). At 2 mm, Arendt et al (2011) reported a total integrated flux density of 244±24 Jy. The total flux density at 3.3 mm was less well constrained due to the small field of view (FOV=40 × 40 ) and the loss of large scale emission.…”
Section: Millimetre and Radio Observationsmentioning
confidence: 99%